Role Management, Educational Satisfaction, and Role Dynamics in Post-Secondary, Re-Entry Women - Mary Ellen Edmondson; David C. Payne; Earline R. Patton (Journal of Research in Rural Education, 1986)
A sample of 42 post-secondary, educational re-entry women completed an extensive questionnaire focusing on background status, role dynamics, satisfaction with and positive effects of their re-entry experience. Results showed that no differences were found between students in a vocationally oriented, job-training program and more traditional, academically oriented re-entry students. Patterns of relationships between the variables in the study revealed that background-status characteristics were not related to positive effects of re-entry while role-dynamic variables were. Implications for educators are discussed.